Teologi Transformatif Jaringan Islam Liberal - Tasmuji Tasmuji (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2011)
This article aims at discussing the extent of the theological significance of Jaringan Islam Liberal (JIL, Islamic Liberal Networks) in Indonesia, founded and led by Ulil Abshar Abdalla. This is because theology is the soul of religious adherents’ life who intend to work through God’s words in the world. JIL has come as an anti-thesis against Islamic fundamentalism movements, which tend to be rigid, intolerant, and exclusive. The facts can be observed, at least, in such mass organizations as Majelis Mujahidin Indonesia (MMI), Laskar Jihad (LJ), Front Pembela Islam (FPI), Ikhwanul Muslimin Indonesia (IMI), and Hizbut Tahrir Indonesia (HTI). The issuance of “the death fatwa” against Ulil Abshar is a part of the textual paradigm held by these mass organizations. To JIL, it is important to bring about inclusive and moderate theological understandings. Then, its mission and agenda are fighting against Islamic fundamentalists’ understanding as they are considered obstacles to the advance of the Muslim community. Here is the important role of the theology that has to be made as a basis of liberation and freedom for the weak community; then, it will be truly meaningful for the weak and poor people.